Design of Food Ordering Application in Teaching Factory Nutrition Care Center in Supporting Zero Stunting - Santi, Maya Weka; Husin, Husin; Rachmawati, Ervina (International Journal of Healthcare and Information Technology, 2024)
Jember Regency was in the spotlight because the prevalence of stunted toddlers has reached the highest rank in East Java with a figure of 34.9% in 2022. Teaching Factory Nutrition Care Center (NCC) has nutritional catering services with Managed Health Meal and Kids Meal packages. However, the ordering process was still done via telephone or chat from social media groups. The research objective was to generate the online application for ordering food at the Teaching Factory NCC to accelerate zero stunting program. It used waterfall method contains of system investigation, system analysis, system design, system implementation, and system maintenance. Meanwhile, this article limited to system design. The results showed that NCC Food facilitates clients/ patients to order nutritious food online according to nutritional adequacy rate needs, particularly for stunted toddlers.